Investigation of the Effect of Physiotherapists' Basic Psychological Needs in Leisure on Life Satisfaction with Structural Equation Model - Ercan Zorba; Gökhan Dokuzoğlu; Muhammed Ömer Eren (Türk Spor ve Egzersiz Dergisi)
This study aimed to examine the effect of physiotherapists' basic psychological needs in leisure on life satisfaction. Relational screening method was used in our study which was conducted according to the general screening model. The data were collected using the personal information form developed by the researchers in the first part, the Basic Psychological Needs Scale in Leisure Activity (BPNSLA) in the second part, and the Life Satisfaction Scale in the third part. The data were analysed with AMOS 21.0 and SPSS 25.0 package programmes. According to the result of the Independent Sample T-test between the Basic Psychological Needs in Leisure Activity and Life Satisfaction of the participants, a statistically significant difference was detected in favour of male participants only in the variable of relatedness, and according to the result of the Anova test between professional experience variables and Basic Psychological Needs in Leisure activity and Life Satisfaction, a statistically significant difference was detected in the total score of Basic Psychological Needs in Leisure activity, competence and relatedness sub-dimensions. Moreover, according to the result of the Independent Sample T-Test between marital status variables and Basic Psychological Needs in Leisure Activity and Satisfaction with Life, a statistically significant difference was detected in all variables except the relatedness variable to Basic Psychological Needs in Leisure Activity, and according to the result of the ANOVA test between Weekly Leisure variable and Basic Psychological Needs in Leisure Activity and Satisfaction with Life, a statistically significant difference was detected only in the autonomy sub-dimension of Basic Psychological Needs in Leisure Time (p